2005
DOI: 10.1203/01.pdr.0000148716.71231.81
|View full text |Cite
|
Sign up to set email alerts
|

Final Height in Short Children Born Small for Gestational Age Treated with Growth Hormone

Abstract: The aim of this observational study was to assess the longterm growth responses to GH treatment of children born small for gestational age (SGA). GH treatment was begun before puberty and continued to final height (FH). Seventy-seven short (height SD score below Ϫ2) prepubertal children born SGA (below Ϫ2 SD for birth weight and/or birth length), with a broad range of GH secretory capacity, were treated with GH in a daily dose of 33 g/kg (0.1 U/kg), beginning before the onset of puberty. We observed a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 35 publications
10
106
0
13
Order By: Relevance
“…Some of these children do not catch up (1,2) and remain short. They may benefit from GH therapy (3)(4)(5). This subgroup is designated in this article as short SGA (SSGA).…”
mentioning
confidence: 99%
“…Some of these children do not catch up (1,2) and remain short. They may benefit from GH therapy (3)(4)(5). This subgroup is designated in this article as short SGA (SSGA).…”
mentioning
confidence: 99%
“…Studies on the effects of GH for treatment of short stature of different etiologies usually included children born prematurely, especially those involving children born SGA (101,102). GH treatment was approved by the US Food and Drugs Administration in 2001 for children born SGA who fail to manifest catch-up growth by the age of 2 years.…”
Section: Growth Hormone Treatmentmentioning
confidence: 99%
“…Several studies have demonstrated that growth hormone treatment effectively induces catch-up growth in prepubertal short SGA children (Dahlgren & Wikland, 2005;de Zegher et al, 2006;Sas et al, 1999). Adult height data from a Dutch multicenter study demonstrated that 85% of children reached a height above -2 SDS and 98% reached a height within the target height range (Van Pareren et al, 2003) (Figure 4).…”
Section: Effects On Linear Growthmentioning
confidence: 99%